2016
DOI: 10.1016/j.biocontrol.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of sentinel egg masses of the exotic invasive stink bug Halyomorpha halys (Stål) in Mid-Atlantic USA ornamental landscapes

Abstract: Biological invasions have far reaching effects on native plant and arthropod communities. This study evaluated the effect of natural enemies on eggs of the exotic invasive brown marmorated stink bug Halyomorpha halys (Stål) in experimental plots comprising species pairs of 16 ornamental trees and shrub genera from either Eurasia or North America and in wooded areas adjacent to the plots. Sentinel egg masses were placed on leaves of Acer, Cercis, Hydrangea, and Prunus in the plots and in seven genera of trees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…When comparing the activity of parasitoids within the three years of the study, patterns were similar in 2014 and 2015, but in 2016 it was slightly delayed for unknown reasons. Overall predation was low generally low in spring, but progressively increased from May onwards in agreement with Cornelius et al ().…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When comparing the activity of parasitoids within the three years of the study, patterns were similar in 2014 and 2015, but in 2016 it was slightly delayed for unknown reasons. Overall predation was low generally low in spring, but progressively increased from May onwards in agreement with Cornelius et al ().…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, surveys performed in invaded areas in the United States showed that Anastatus spp. were the most efficient endemic parasitoids attacking sentinel H. halys egg masses (Cornelius et al, ; Dieckhoff et al, ; Haye, Fischer, et al, ; Jones et al, ). In addition, Anastatus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These laboratory results were later supported by (1) field observations of native parasitoids frequently attending sentinel H. halys egg masses in the field (indicating attack) with low associated offspring emergence levels (Cornelius et al. , b); (2) some species of native parasitoids emerging from sentinel egg masses that had been freeze‐killed before placement in the field (and thus lost their resistance to parasitoid development through an as‐yet unknown mechanism); and (3) high rates of H. halys egg abortion in sentinel egg masses placed in the field, some of which was directly attributable to unsuccessful parasitoid development (as determined by dissection), as well as a large amount of unassigned egg mortality that could possibly represent undetected additional parasitoid‐induced abortion (Cornelius et al. , b).…”
Section: Resultsmentioning
confidence: 82%
“…, b); (2) some species of native parasitoids emerging from sentinel egg masses that had been freeze‐killed before placement in the field (and thus lost their resistance to parasitoid development through an as‐yet unknown mechanism); and (3) high rates of H. halys egg abortion in sentinel egg masses placed in the field, some of which was directly attributable to unsuccessful parasitoid development (as determined by dissection), as well as a large amount of unassigned egg mortality that could possibly represent undetected additional parasitoid‐induced abortion (Cornelius et al. , b). A previous study has predicted an indirect benefit to native stink bugs (some of which could become pests if their density increases) resulting from unsuccessful attack of H. halys by native parasitoids (Abram et al.…”
Section: Resultsmentioning
confidence: 99%